Mosaic Turner Syndrome and Hypogonadotropic Hypogonadism in a 17-Year-Old Female: A Diagnostic Dilemma with Possible Kallmann Syndrome - Muhammad Alif; Artha Falentin Putri Susilo; Hanom Husni Syam; Dian Tjahyadi; Anita Rachmawati (Indonesian Journal of Obstetrics & Gynecology Science, 2026)
Introduction: Primary amenorrhea, defined as the absence of menstruation by age 15, has a broad differential diagnosis, including anatomical, endocrine, hypothalamic-pituitary, and genetic causes. Turner syndrome and Kallmann syndrome are two distinct etiologies with different pathophysiological mechanisms. Turner syndrome is characterized by hypergonadotropic hypogonadism due to gonadal dysgenesis, whereas Kallmann syndrome results from gonadotropin-releasing hormone (GnRH) deficiency and is often associated with anosmia.Case Presentation: A 17-year-old female was referred with primary amenorrhea and absent secondary sexual development. Physical examination revealed Tanner Stage I breast and pubic hair development, with no reported olfactory disturbances. Hormonal assays indicated hypogonadotropic hypogonadism, with low FSH, LH, and estradiol levels. Pelvic ultrasonography revealed a hypoplastic uterus and non-visualized ovaries. Cranial MRI showed pituitary hypoplasia and bilateral agenesis of the olfactory bulbs, suggestive of Kallmann syndrome. However, karyotype analysis revealed a mosaic 45,X/46,XX pattern, consistent with Turner syndrome. This combination of clinical, hormonal, imaging, and cytogenetic findings posed a unique diagnostic dilemma.Discussion: The overlapping features of Turner and Kallmann syndromes make this case highly unusual. Turner syndrome typically presents with hypergonadotropic hypogonadism, whereas Kallmann syndrome is characterized by hypogonadotropic hypogonadism, often with anosmia. Comprehensive evaluation, including cytogenetic analysis and MRI, was essential for accurate diagnosis. Management focused on pubertal induction with hormone replacement therapy and appropriate genetic and systemic evaluation.Conclusion: This case underscores the diagnostic complexity of primary amenorrhea with overlapping features of Turner and Kallmann syndromes. Accurate diagnosis requires integrated hormonal, imaging, and cytogenetic evaluation, with management focused on hormonal correction and long-term supportive care.